Effectiveness of imazaquin seed treatment on Striga gesnerioides control and growth traits of seven cowpea genotypes - Lado, A.; Hussaini, M.A.; Kamara, A. (Springer, 2018)
Cultural and biological control measures have failed to provide satisfactory management of Striga gesnerioides, a major biotic constraint to cowpea production in sub-Saharan Africa. Field trials were conducted to evaluate the efficacy of imazaquin seed treatment (at 0.00, 0.06, and 0.24 kg a.i. ha−1) on Striga gesnerioides control and the growth of seven cowpea genotypes (Achishiru, IT97K-1263, IT97K-390-2, IT98K-133-1-1, TVU-1283, TVU-1542, and TVU-1908) at the Teaching and Research Farm of the Faculty of Agriculture of Bayero University, Kano, Nigeria, during the rainy seasons of 2010 and 2011. Treating the seeds with imazaquin at 0.24 kg a.i. ha−1 produced the lowest number of striga stand−1. Across herbicide rates, Achishiru had most S. gesnerioides; IT97K-1263 had the fewest. The results indicated that the untreated control recorded the highest number. The untreated TVU-1283 produced the fewest branches; Achishiru produced the least dry matter while IT97K-1263 had the most branches and dry matter in 2010 and 2011 rainy seasons. Application of 0.24 kg a.i. ha−1 to IT97K-390-2 consistently produced the highest branches and dry matter; Achishiru produced the fewest branches and least dry matter in 2010 and 2011 seasons. Treating IT97K-390-2, IT98K-133-1-1, and TVU-1542 with imazaquin at 0.24 kg a.i. ha−1 provided an effective means of managing striga in cowpea and enhanced the growth characters of these genotypes.